Situation Actuelle Et Facteurs Influençant L’allaitement Dans La Ville De Rabat Au Maroc A Propos D’une Enquête Chez 275 Mères - Houssaini, Zineb Sqalli; Inekac, Sultana; Hassani, Maryam Benbachir; Ouhssine, Mohammed; Guessous, Zineb (European Scientific Journal, ESJ, 2017)
Breastfeeding is the most ideal type of feeding for all infants; it is the optimal food for both newborns and young infants. It has no equal as it is adjusted to their needs and their abilities. Breastfeeding has many advantages for the child as well as the mother. The main objective of this study is to evaluate the current situation of breastfeeding in the region of Rabat city; assess the prevalence of breastfeeding and the different methods adopted; and identify the rationale behind the choice of each feeding form, the weaning methods, and the age of diversification of the child's diet. To meet these objectives, a survey was conducted through a questionnaire of 31 questions on a sample of 275 women with children aged between 0 and 3 years and thus with a recent breastfeeding experience. - The women surveyed were aged between 18 and 38 years, 55 % are under 30 years. - 95% of women surveyed are from a medium or low social economical class background, 42.5% of them are illiterate, 16% of them have a primary or secondary school level, while 41.5% have a higher level of education. - Primiparous represent 32% of participants, while 68% are multiparous. The average number of children per woman is 2.21. - The prevalence of breastfeeding represents 89%. 40% of participants have opted for exclusive breastfeeding while almost 50% have chosen mixed feeding. Finally, 11% of participants have adopted artificial feeding. - Only 34% of respondents could breastfeed their newborn during the first 24 hours after delivery, and more than half of the respondents (54%) did it only the second day post-delivery. - The average duration of breastfeeding is 7.7 months - Many factors that could impact the choice of the breastfeeding mode were studied during this survey. The inter-factorial analysis showed that the delivery mode, the socio-professional class, the level of education, and the sex of children can have a significant influence on the mode and the frequency of breastfeeding. - 80% of women have already weaned their infants through different ways. The forecast of weaning from breastfeeding diverges according to the breastfeeding mode chosen. The current average age of weaning predicted is estimated to 6.9 months. - The average age of introducing another feeding alternative which is different from breastfeeding (water, orange juice, formula milk etc.) is estimated to 2.38% months. It diverges depending on the type of food that was introduced. - The average age of introducing industrial milk is estimated to 3 months accompanied by 3 feeding bottles per day on an average. To face the exclusive breastfeeding regression tendency and the very early introduction of formula milk, a promotional awareness campaign on breastfeeding of mothers is compulsory. The factors identified to be influencing the mode of breastfeeding represent an alternative way to be examined. This is for the purpose of elaborating direct actions of the promotion of breastfeeding for women with low willingness to breastfeed.